HUBUNGAN KONSEPSI BELAJAR-MENGAJAR TERHADAP KECENDERUNGAN BELAJAR SEPANJANG HAYAT PADA MAHASISWA PENDIDIKAN EKONOMI - Fatma Inayatul Kholisoh; Kristiani Kristiani; Leny Noviani (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2024)
Thisa research aims to explore the correlation of conceptions of teaching and learning on lifelong learning tendencies. This research uses quantitative research methods, data collection using questionnaires to a population of 317 Economic Education students at Sebelas Maret University, Surakarta, class of 2019, 2020 and 2021 and 177 research subjects. The sampling technique was proportioned random sampling. Measurements were carried out on the conception of teaching and learning and lifelong learning tedencies. Statistical analysis uses correlation and regression methods to evaluate the relationship between these variables. The results of the research show that (1) there is a positive and significant relationship between the constructivist conception of teaching-learning and lifelong learning tendencies (2) there is a low positive relationship between the traditional conception of teaching-learning and it does not have a significant effect on lifelong learning tendencies.